Multimorbidity Accumulation Among Middle-Aged Americans: Differences by Race/Ethnicity and Body Mass Index. Issue 2 (21st April 2021) - Botoseneanu, Anda; Markwardt, Sheila; Nagel, Corey L; Allore, Heather G; Newsom, Jason T; Dorr, David A; Quiñones, Ana R
Abstract: Background: Obesity and multimorbidity are more prevalent among U.S. racial/ethnic minority groups. Evaluating racial/ethnic disparities in disease accumulation according to body mass index (BMI) may guide interventions to reduce multimorbidity burden in vulnerable racial/ethnic groups. Method: We used data from the 1998–2016 Health and Retirement Study on 8 106 participants aged 51–55 at baseline. Disease burden and multimorbidity (≥2 co-occurring diseases) were assessed using 7 chronic diseases: arthritis, cancer, heart disease, diabetes, hypertension, lung disease, and stroke. Four BMI categories were defined per convention: normal, overweight, obese class 1, and obese class 2/3. Generalized estimating equations models with inverse probability weights estimated the accumulation of chronic diseases. Results: Overweight and obesity were more prevalent in non-Hispanic Black (82.3%) and Hispanic (78.9%) than non-Hispanic White (70.9 %) participants at baseline. The baseline burden of disease was similar across BMI categories, but disease accumulation was faster in the obese class 2/3 and marginally in the obese class 1 categories compared with normal BMI. Black participants across BMI categories had a higher initial burden and faster accumulation of disease over time, while Hispanics had a lower initial burden and similar rate of accumulation, compared with Whites. Black participants, including those with normal BMI, reach the multimorbidity threshold 5–6 years earlier compared with White participants. Conclusions: Controlling weight and reducing obesity early in the lifecourse may slow the progression of multimorbidity in later life. Further investigations are needed to identify the factors responsible for the early and progressing nature of multimorbidity in Blacks of nonobese weight.